Artificial Intelligence and machine learning techniques for civil engineering - Plevris, Vagelis 1976-; Ahmad, Afaq; Lagaros, Nikos D. (IGI Global, 2023)
This reference book offers state-of-the-art contributions in the area of AI and its applications in the field of civil engineering presenting methods and implementation of AI and machine learning in multiple facets of civil engineering
Keywords: Civil engineering -- Data processing; Artificial intelligence; Machine learning